Environmental Factors to Malaria Incidence : A Literature Review - nani, Nani Sri Untari; Rahardjo, Mursid; Martini (Journal of Community Medicine and Public Health Research, 2024)
Malaria remains a major public health concern in Indonesia, particularly due to its high mortality rate among children under five, accounting for approximately two-thirds of all cases. The disease is transmitted by female Anopheles mosquitoes, which carry the Plasmodium parasite. In 2019, malaria caused 409,000 deaths globally, with 229 million cases reported, particularly in remote areas with poor access to healthcare, commonly in low-income countries. This literature review highlighted the environmental risk factors contributing to malaria incidence, based on studies from 24 scientific journals using data from the Sinta and Scopus databases. The study identified key environmental factors, including physical, chemical, biological, and socio-cultural elements, with the most significant risk linked to vector breeding sites. Among the reviewed articles, 62.5% (15 out of 24) found a statistically significant association between the presence of mosquito breeding sites and malaria incidence. Additional risk factors included the use of mosquito nets, housing conditions (specifically wall density), and nighttime outdoor activities. Effective malaria control measures require addressing these environmental factors, as they play a crucial role in the disease’s transmission. Strategies to disrupt the transmission cycle include eliminating mosquito breeding sites, applying larvicides to stagnant water, cleaning vector resting areas, promoting the use of insecticide-treated nets, and implementing Indoor Residual Spraying (IRS). A community-based, integrated approach to environmental management is essential to reducing malaria transmission and controlling its spread in affected regions.